2013
DOI: 10.1177/1757975913476905
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing, facilitating and reinforcing factors of healthy and unhealthy food consumption in schoolchildren: a study in Ouagadougou, Burkina Faso

Abstract: Abstract:Objective: African schoolchildren's dietary habits are likely changing in the realm of the nutrition transition, particularly in urban areas, but data on their diet and on determinants are scanty. In order to design relevant interventions for this priority target group, the study aimed to assess food habits and their determinants in schoolchildren of Ouagadougou. Methods: In a cross-sectional survey, fifth-grade schoolchildren filled during school hours a questionnaire to assess consumption frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 37 publications
2
37
1
1
Order By: Relevance
“…Unhealthy eating in West Africa begins early in life. Only 4 % of fifth-grade children aged 12 years in Ouagadougou reported eating fruit or vegetables daily, whereas nearly five times as many ate ice pop daily (21) . Those reporting daily consumption of cakes or candies were twice those eating fruit, vegetables or legumes daily.…”
Section: Unhealthy Eating In Childhoodmentioning
confidence: 99%
“…Unhealthy eating in West Africa begins early in life. Only 4 % of fifth-grade children aged 12 years in Ouagadougou reported eating fruit or vegetables daily, whereas nearly five times as many ate ice pop daily (21) . Those reporting daily consumption of cakes or candies were twice those eating fruit, vegetables or legumes daily.…”
Section: Unhealthy Eating In Childhoodmentioning
confidence: 99%
“…The average age of schoolchildren was 10.92 ± 1.32 years in this study, and is approximately the same as the study population of on predisposing, facilitating and enhancing food consumption factors health and non-health among schoolchildren in Ouagadougou [12]. Overweight / Obesity N = number of respondents; BMI = body mass index for age; OR = Odds Ratio; P-value is significant at p <0.05 Table 4: Multivariate logistic regression between school performance and socio-demographic characteristics of schoolchildren in Yopougon and Bingerville (N = 426)…”
Section: Relationship Between Good School Performance and Socio-demogmentioning
confidence: 67%
“…Thus, the question asked to students was, during 7 days was: how many days did you eat these foods? These different foods concerned vegetables, fruits, meat, fish, liver, tofu and caramel, candy and chewing gum, biscuits and chocolates, yoghurt and dairy products and sweetened beverages [12].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper [23], we reported that although the prevalence of overweight/obesity in urban schoolchildren of Ouagadougou was still low, it was double that reported 10 years ago [24]. Eating behaviours conducive to obesity tended to be widespread in these schoolchildren [25]. Other risk factors include early nutrition and family history.…”
Section: Introductionmentioning
confidence: 75%